Exploring membrane protein structural features by oxidative labeling and mass spectrometry. (October 2012) - Konermann, Lars; Pan, Yan
Despite their biological importance, the structural characterization of integral membrane proteins (IMPs) by x-ray crystallography and NMR spectroscopy remains challenging. Hence, there is a need for complementary approaches that are capable of probing IMP conformational features in a robust fashion. Covalent labeling relies on the principle that solvent accessible regions can be modified by reactive species, whereas buried segments are protected. The readout of the labeling pattern is conducted by mass spectrometry. Hydroxyl radical (·OH) introduces oxidative modifications at amino acid side chains. In this article, the authors discuss the application of ·OH labeling for the structural interrogation of IMPs. Kyte-Doolittle hydropathy analyses are widely used for generating IMP topology models. The validation of these models by mutational techniques is labor intensive. ·OH labeling can readily distinguish transmembrane elements from solvent-exposed loops, thereby providing an alternative topology validation tool. For IMPs with published crystal structures, oxidative modifications can report on functionally relevant dynamic features that are invisible in the static x-ray data. The coupling of pulsed ·OH labeling with rapid mixing techniques represents a novel approach for studying IMP folding kinetics. In conclusion, ·OH labeling is a versatile tool that can provide insights into the structure and dynamics of IMPs.